ANALYSIS OF CONSUMER BEHAVIOR TOWARDS PURCHASING DECISIONS FOR KING FRIED CHICKEN IN SYIAH KUALA - Jasmine Mardhina Qamarani FP; Dian Asri (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study analyzes consumer behavior factors influencing purchasing decisions for King Fried Chicken in Syiah Kuala, Banda Aceh. In the competitive fast-food industry, a deep understanding of consumer behavior is crucial for business sustainability. The research uses a quantitative approach with a causality survey design. Primary data was collected from 150 King Fried Chicken consumers in Banda Aceh through structured questionnaires, employing purposive sampling. The independent variables include cultural (X1), social (X2), personal (X3), and psychological (X4) factors, while purchasing decisions (Y) serve as the dependent variable. All items were measured using a 5-point Likert scale. Validity and reliability tests confirmed that all items were valid and the instrument was reliable (Cronbach’s Alpha > 0.60). Classical assumption tests (normality, multicollinearity, and heteroscedasticity) were met, ensuring regression model feasibility. The t-test results showed that cultural, personal, and psychological factors had a positive and significant influence on purchasing decisions, while social factors were insignificant. Simultaneously, the F-test confirmed that all four factors collectively had a significant effect. The coefficient of determination (R²) indicated that 63.8% of purchasing decision variations were explained by these variables, with the remainder influenced by external factors.